Global burden of disease attributable to illicit drug use and dependence: findings from the Global Burden of Disease Study 2010 - Degenhardt, Louisa; Whiteford, Harvey A; Ferrari, Alize J; Baxter, Amanda J; Charlson, Fiona J; Hall, Wayne D; Freedman, Greg; Burstein, Roy; Johns, Nicole; Engell, Rebecca E; Flaxman, Abraham; Murray, Christopher JL; et al. (The Lancet (British edition), 2013)
No systematic attempts have been made to estimate the global and regional prevalence of amphetamine, cannabis, cocaine, and opioid dependence, and quantify their burden. We aimed to assess the prevalence and burden of drug dependence, as measured in years of life lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life years (DALYs). We conducted systematic reviews of the epidemiology of drug dependence, and analysed results with Global Burden of Diseases, Injuries, and Risk Factors Study 2010 (GBD 2010) Bayesian meta-regression technique (DisMod-MR) to estimate population-level prevalence of dependence and use. GBD 2010 calculated new disability weights by use of representative community surveys and an internet-based survey. We combined estimates of dependence with disability weights to calculate prevalent YLDs, YLLs, and DALYs, and estimated YLDs, YLLs, and DALYs attributable to drug use as a risk factor for other health outcomes. Illicit drug dependence directly accounted for 20·0 million DALYs (95% UI 15·3–25·4 million) in 2010, accounting for 0·8% (0·6–1·0) of global all-cause DALYs. Worldwide, more people were dependent on opioids and amphetamines than other drugs. Opioid dependence was the largest contributor to the direct burden of DALYs (9·2 million, 95% UI 7·1–11·4). The proportion of all-cause DALYs attributed to drug dependence was 20 times higher in some regions than others, with an increased proportion of burden in countries with the highest incomes. Injecting drug use as a risk factor for HIV accounted for 2·1 million DALYs (95% UI 1·1–3·6 million) and as a risk factor for hepatitis C accounted for 502 000 DALYs (286 000–891 000). Suicide as a risk of amphetamine dependence accounted for 854 000 DALYs (291 000–1 791 000), as a risk of opioid dependence for 671 000 DALYs (329 000–1 730 000), and as a risk of cocaine dependence for 324 000 DALYs (109 000–682 000). Countries with the highest rate of burden (>650 DALYs per 100 000 population) included the USA, UK, Russia, and Australia. Illicit drug use is an important contributor to the global burden of disease. Efficient strategies to reduce disease burden of opioid dependence and injecting drug use, such as delivery of opioid substitution treatment and needle and syringe programmes, are needed to reduce this burden at a population scale. Australian National Health and Medical Research Council, Australian Government Department of Health and Ageing, Bill & Melinda Gates Foundation.